2021
DOI: 10.1021/acsami.1c14135
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Responsive and ROS-Augmented Nanoplatform for Chemo/Photodynamic/Chemodynamic Combination Therapy of Triple Negative Breast Cancer

Abstract: Integrating chemodynamic therapy (CDT) and photodynamic therapy (PDT) into one nanoplatform can produce much more reactive oxygen species (ROS) for tumor therapy. Nevertheless, it is still a great challenge to selectively generate sufficient ROS in tumor regions. Meanwhile, CDT and PDT are restricted by insufficient H 2 O 2 content in the tumor as well as by the limited tumor tissue penetration of the light source. In this study, a smart pH/ROS-responsive nanoplatform, Fe 2+ @UCM-BBD, is rationally designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Lei et al prepared pH-responsive nanoparticles co-encapsulated with DOX and APAP, which were released at 56.5% and 61.8%, respectively, under an acidic endosomal/lysosomal environment, synergistically promoting OH • generation by the Fenton reaction [ 86 ]. Cho et al prepared dual (pH- and redox-)responsive magnetic nanoparticles that promote drug release under low pH and high GSH concentrations [ 87 ], and Chen et al developed a pH/ROS-responsive multifunctional nanoplatform that inhibits tumor through chemo/photodynamic/chemodynamic combinations [ 88 ]. Jia et al prepared multifunctional nanoparticles with a core-shell structure encapsulating Fe 3 O 4 and demonstrated that simultaneous photothermal and chemodynamic therapy is possible [ 89 ].…”
Section: Use Of the Fenton Reaction For Drugsmentioning
confidence: 99%
“…Lei et al prepared pH-responsive nanoparticles co-encapsulated with DOX and APAP, which were released at 56.5% and 61.8%, respectively, under an acidic endosomal/lysosomal environment, synergistically promoting OH • generation by the Fenton reaction [ 86 ]. Cho et al prepared dual (pH- and redox-)responsive magnetic nanoparticles that promote drug release under low pH and high GSH concentrations [ 87 ], and Chen et al developed a pH/ROS-responsive multifunctional nanoplatform that inhibits tumor through chemo/photodynamic/chemodynamic combinations [ 88 ]. Jia et al prepared multifunctional nanoparticles with a core-shell structure encapsulating Fe 3 O 4 and demonstrated that simultaneous photothermal and chemodynamic therapy is possible [ 89 ].…”
Section: Use Of the Fenton Reaction For Drugsmentioning
confidence: 99%
“…Overall, the results of western blotting and apoptosis analysis illustrate that the photothermal performance of AgBiSe 2 under 1064 nm NIR irradiation can upregulate the expression of Hsp70 and Cas 3 in 4T1 cells, thus inducing apoptosis and necrosis, and finally causing cell death. 53,54…”
Section: In Vitro Anticancer Testmentioning
confidence: 99%
“…However, the insufficient concentration of H 2 O 2 in TME limits the practical application [ 22 , 23 ]. PDT is also a ROS-mediated therapy with spatio-temporal selectivity in response to localized specific laser stimulation [ 24 ], which generates highly cytotoxic ROS ( 1 O 2 ) by transferring light energy to surrounding O 2 through localized light radiation. However, PDT is heavily dependent on tissue oxygen concentration.…”
Section: Introductionmentioning
confidence: 99%